2019
DOI: 10.1039/c9sc01345h
|View full text |Cite
|
Sign up to set email alerts
|

Vinylphosphonites for Staudinger-induced chemoselective peptide cyclization and functionalization

Abstract: Vinylphosphonites react in chemoselective Staudinger-phosphonite reactions (SPhR) with azides to form vinylphosphonamidates for the subsequent modification of cysteine residues in peptides and proteins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
63
1
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 58 publications
(81 citation statements)
references
References 52 publications
0
63
1
9
Order By: Relevance
“…Recently, we introduced unsaturated phosphonamidates for the selective and irreversible modification of cysteine residues in proteins and antibodies . We described the synthesis of NHS‐modified ethynylphosphonamidate building block 2 and demonstrated that hydrophilic diethylene glycol substitution at the phosphonamidate ester residue could drastically increase the water solubility .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we introduced unsaturated phosphonamidates for the selective and irreversible modification of cysteine residues in proteins and antibodies . We described the synthesis of NHS‐modified ethynylphosphonamidate building block 2 and demonstrated that hydrophilic diethylene glycol substitution at the phosphonamidate ester residue could drastically increase the water solubility .…”
Section: Introductionmentioning
confidence: 99%
“…Phosphoramidates and other phosphate‐based constructs have become useful tools in chemical biology as probes for biochemical processes, such as membrane transport, protein phosphorylation and conjugation. [1a] In addition, these compounds can also be used as alternatives to phosphorothioate antisense oligonucleotides or as candidates for the development of smart materials, including biodegradable polymers, or sensors for medical applications such as diagnosis[1b], , and drug delivery…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, a number of ''selfhydrolysing'' maleimides have now been developed, with ring-opening catalysed by adjacent functional groups such as primary amine, polyethylene glycol (PEG) and N-aryl amongst the most promising. [76][77][78][79] Other reagents including a-halocarbonyls, 80 palladium oxidative-addition complexes, 81 ethynylphosphonamidates, 82,83 vinylphosphonites 84 and ethynylbenziodoxolones 85 have also been used to synthesise ADCs with stable thioether bonds via modification of reduced interchain disulfides ( Fig. 5B).…”
Section: Stochastic Conjugation With Naturally Occurring Amino Acidsmentioning
confidence: 99%